2020
DOI: 10.1177/0892020620959748
|View full text |Cite
|
Sign up to set email alerts
|

Research on school principals in the Gulf states: A systematic review of topics and conceptual models

Abstract: In view of the growing emphasis by educational leadership and management (EDLM) scholars on diversifying the existing knowledge base in the field, this review of research analysed topics and conceptual models employed in 104 studies on school principals from the Arabian Gulf states published between 2000 and 2019. Systematic review methods were used to identify relevant studies documented in Arabic databases hosted by Dar Almandumah. Information was extracted from the articles and analysed using quantitative m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 45 publications
(86 reference statements)
2
17
0
Order By: Relevance
“…Consistent with the findings of Hammad and Alazmi (2020), our results revealed that few studies have focused on topical foci such as preparation and development, school improvement, equality, social justice and cultural contexts. The results of this study are in line with those of other studies in the developing societies and imply that the Iranian scholars did not pay any attention to the impact of school leaders on students' learning (Bellibaş and G€ um€ uş, 2019;Hammad and Alazmi, 2020;Hammad and Hallinger, 2017). The disinclination to study the influence of leadership on student learning Research on school principals in Iran outcomes might be due to the less frequent use of the comprehensive conceptual models and quantitative methods in this literature (Hallinger, 2018).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with the findings of Hammad and Alazmi (2020), our results revealed that few studies have focused on topical foci such as preparation and development, school improvement, equality, social justice and cultural contexts. The results of this study are in line with those of other studies in the developing societies and imply that the Iranian scholars did not pay any attention to the impact of school leaders on students' learning (Bellibaş and G€ um€ uş, 2019;Hammad and Alazmi, 2020;Hammad and Hallinger, 2017). The disinclination to study the influence of leadership on student learning Research on school principals in Iran outcomes might be due to the less frequent use of the comprehensive conceptual models and quantitative methods in this literature (Hallinger, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…Kılınç and Gümüş, 2020; Murphy, 2019; Walker and Qian, 2015; Wang et al , 2017), leadership roles/practices (e.g. Hammad and Alazmi, 2020; Walker and Qian, 2015), leadership models/styles (e.g. Murphy, 2019; Oplatka and Arar, 2017; Szeto et al , 2015; Wang et al , 2017), leadership antecedents (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Fulfilling this mandate, generally, Senior High Schools have compiled the Education Unit Level Curriculum, which is an operational curriculum and implemented in each educational unit. Besides, it functions as a guideline for implementing learning activities to accomplish particular goals of education [1].…”
Section: Introductionmentioning
confidence: 99%
“…Beside its insignificant contribution to the global educational scholarship, Arab educational research has also been criticized for some methodological and conceptual limitations. These include excessive reliance on quantitative research approaches and data collection techniques, an evident tendency to employ simple conceptual models that are unable to address the complex nature of educational phenomenon (see Hammad & Alazmi, 2020; Hammad & Hallinger, 2017; Hammad et al, 2020), in addition to focusing on irrelevant issues rather than addressing real problems facing schools and education systems in Arab societies (Sakran, 2010). The latter has led to what Karami-Akkary and El Sahib (2019) describe as “blind spots” in the Arab educational knowledge base.…”
Section: Educational Research In the Arab Region: An Overviewmentioning
confidence: 99%